2014
DOI: 10.1186/s12913-014-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal health research in the remote Kimberley: an exploration of perceptions, attitudes and concerns of stakeholders

Abstract: BackgroundFor decades Indigenous peoples have argued for health research reform claiming methods used and results obtained often reflect the exploitative history of colonisation. In 2006 the Kimberley Aboriginal Health Planning Forum (KAHPF) Research Subcommittee (hereafter, the Subcommittee) was formed to improve research processes in the remote Kimberley region of north Western Australia. This paper explores the major perceptions, attitudes and concerns of stakeholders in the Subcommittee.MethodsQualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
(33 reference statements)
2
28
0
Order By: Relevance
“…However, there appear to be few examples of their implementation in practice. 50 In this review, we identified outcomes related to evaluating interventions, services or training in seven studies 19,20,2729,33,34,36,37 or assessing resources in two studies. 25,31 These outcomes indicate potential impact at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…However, there appear to be few examples of their implementation in practice. 50 In this review, we identified outcomes related to evaluating interventions, services or training in seven studies 19,20,2729,33,34,36,37 or assessing resources in two studies. 25,31 These outcomes indicate potential impact at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…These perspectives form the basis of a sound social‐ecological approach 17 . This multi‐layered perspective needs considerable attention in Aboriginal health, where research has traditionally been done on, not with, Aboriginal people 18,19 . Discussion focused on improving the conduct of Aboriginal health research has stressed the importance of engaging with the community to address community priorities and goals before the design process.…”
Section: Settingmentioning
confidence: 99%
“…In addition, facilitating local ownership, control, and the development of research capacity is essential to respecting cultural protocols. Specific recommendations to improve research conduct include working with community and local organisations to embed research in local services, employment of local people in research, having a flexible research approach, and patience to allow sufficient time for consultation and data collection 19 …”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations